Adaptabilidade e estabilidade de genótipos de soja em Minas Gerais - Correia, Wanessa Rosa (2007)
The objective of this work was to analyze the stability and adaptability of 11 soybean genotypes, where 8 lines belonged to the Soybean breeding program of UFU and 3 commercial cultivars were used as controls: M-Soy 8400, MG/BR-46 Conquista and M-Soy 6101. The experimental design used was randomized blocks, with three replications. The study was done in 2004/2005 and 2005/2006 harvest in Uberlândia and Uberaba counties (Minas Gerais state), where years were considered as places by the Soybean breeding program of UFU. Individual and combined statistical analyses were performed considering genotype effects as fixed and environment effects as variable. The methods to analyze were AMMI procedure ( additive main effect and multiplicative interaction analysis) and ecovalence method. There was average correlation between stability and higher mean yields by the ecovalence method. By the AMMI procedure, the genotypes G9, G5, G7, G1 and environment Uberlândia 2004/2005 (A1 and A2) were the most stables, also presenting good average yields, demonstrating that they are the most promising for cultivar recommendation.